Exponential synchronization of stochastic coupled oscillators networks with delays. Issue 6 (26th April 2017) - Zhang, Chunmei; Li, Wenxue; Wang, Ke
Abstract : This paper investigates the exponential synchronization problem of coupled oscillators networks with disturbances and time-varying delays. On basis of graph theory and stochastic analysis theory, a feedback control law is designed to achieve exponential synchronization. By constructing a global Lyapunov function for error network, both p th moment exponential synchronization and almost sure exponential synchronization of drive-response networks are obtained. Finally, a numerical example is given to show the effectiveness of the proposed criteria.